Application of Intermediate Moment-Resisting Frame for Seven-Story Hotel Structure Building in Pontianak - Figo, Luis; Yusuf, Muhammad; Supriyadi, Asep (Jurnal Teknik Sipil, 2025)
As part of the city"™s economic growth, constructing hotels in Pontianak requires planning considering earthquake resistance to protect building occupants and minimize material damage and the negative economic impacts of earthquakes. Therefore, this study aims to apply the Intermediate Moment Resisting Frame (SRPMM) system to the structural design of a 7-story hotel building in Pontianak. In this study, the building structure is designed using reinforced concrete with the SRPMM system, which can provide adequate stability against earthquake loads. This research includes load calculations, structural analysis, earthquake resistance design, considering the planned structural dimensions, and using structural analysis software to calculate internal forces. The building is classified as KDS C. Thus, the application of SRPMM complies with the necessities set out in SNI 2847-2019 and SNI 1726-2019. The analysis results show that the designed structure meets earthquake opposition requirements according to established standards. This study contributes to developing the application of SRPMM to multi-story buildings, particularly in regions with low to moderate earthquake risks like Pontianak.